Entrepreneurship Education and Graduate Unemployment in Nigeria - ZUBAIR, Oladimeji Mansur’; ALABI, Jimoh Adeniyi; ADEDOTUN, Isiaka Adebayo (International Journal of Educational Management, 2025)
T he objective of this study is to examine entrepreneurship education and graduate unemployment in Nigerian universities. Entrepreneurship education was introduced i universities to reduce the unemployment rate among graduates. It is a form of education which seeks to provide entrepreneurial skills for students so as to be self-employed ant be a job creator after graduation. Despite its objectivities to reduce graduate unemployment in the country, there still persist increase in graduate unemployment i the country. Therefore, this paper seeks to examine entrepreneurship education i Nigerian universities. The paper equally examined entrepreneurship education an graduate unemployment in Nigeria. It further discussed the problem of entrepreneurshi education in Nigerian universities, among which is entrepreneurship educatia curriculum implementation, absent of qualified lecturers/instructon Recommendations were raised, among which is; Universities authorities should ensuw adequate implementation of entrepreneurship education Curriculum and should made as a compulsory course for all students irrespective of their discipline.